Noise properties of micro-cavity lasers - Natsume, Yuki (2014)
The quantum limited linewidth of a laser results from the interaction between the noise generated by spontaneous emission processes and the non-orthogonal modes of the open cavity. This linewidth can be obtained semi-analytically through the scattering matrix (S matrix) of the cavity, or through direct integration of the electromagnetic mode solutions over the entire lasing cavity. This project entails the calculation of the linewidth of 2D micro cavity lasers through these two methods and the results will be compared with the traditional result of Schawlow and Townes.